LINGUAGEM ESCRITA: INSTRUMENTO DE ESCREVENTES-CIDADÃS - Tinoco, Glícia Marili Azevedo de Medeiros (Intercâmbio, 2010)
Through a work of strong social impact, adolescents draw a sociocultural profile of their communities, analyze the public services that are offered (or its inexistence), detect their needs, set out claiming documents to councilors, take part in meetings and go along with this process of citizen legitimacy, which is set up throughout an ethnographic project of collaborative writing.